2010
DOI: 10.1089/gtmb.2010.0059
|View full text |Cite
|
Sign up to set email alerts
|

Association of Methylenetetrahydrofolate Reductase C677T and Cystathionine β-Synthase Polymorphisms in Cardiovascular Disease in the Algerian Population

Abstract: The MTHFR C677T and CBS 844ins68 variants tested in this study, individually or combined, are not associated with CVD in the Algerian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…With this in mind, some studies have correlated the C677T and A1298C polymorphisms within MTHFR gene with elevated levels of plasma homocysteine and/or with an increased risk of CVD [21,38,95,105,129], while other studies have not found such associations [15,59,65,97]. Besides other risk factors involved, ethnic and geographic variations in the allele frequencies of these polymorphisms could perhaps explain these controversial results.…”
Section: Discussionmentioning
confidence: 99%
“…With this in mind, some studies have correlated the C677T and A1298C polymorphisms within MTHFR gene with elevated levels of plasma homocysteine and/or with an increased risk of CVD [21,38,95,105,129], while other studies have not found such associations [15,59,65,97]. Besides other risk factors involved, ethnic and geographic variations in the allele frequencies of these polymorphisms could perhaps explain these controversial results.…”
Section: Discussionmentioning
confidence: 99%
“…S1) [Leclerc et al, 2005;Gueant-Rodriguez et al, 2006]. Although data are limited for African populations, Algeria [Houcher et al, 2010] and Tunisia [Rouissi et al, 2009] in northern Africa have higher frequencies (ß14% and ß11%, respectively) than Benin [Gueant-Rodriguez et al, 2006], Burkina Faso [Angius et al, 2007], and Ghana [Rosenberg et al, 2002] (all <1%) in sub-Saharan Africa. The polymorphism is part of a common haplotype shared among diverse populations, suggesting a shared ancestral history; selective advantage could have assisted in spreading the variant through populations [Rosenberg et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies reported a considerable difference between CVD patients and controls (12)(13)(14)(15), while others had no difference (16)(17)(18).…”
Section: Discussionmentioning
confidence: 88%